2019
DOI: 10.1248/yakushi.18-00115
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Reorganized Training Program Using a Cognitive Behavioral Therapy Approach to Enable Community Pharmacists to Provide Empathic Patient Counseling

Abstract: To enable community pharmacists to provide empathic patient counseling, we developed and validated a training program based on the cognitive behavioral therapy approach (CBT-A) in our previous study. The major focus points of the restructured training program were``inclusion of basic communication skills'',``exemplifying correspondence involving CBT-A using pre-recorded video(VTR)'', and``approach methods for cases where counter-evidence is unavailable''. The training program lasted for 4 h per day, for a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…It can be questioned if a short course of 16 hours would change the communication practice of pharmacists. However, a study from Japan has shown that community pharmacists can become more empathetic and have more satisfied patients after eight hours of simulation training (Tanuma et al, 2019). The pharmacists in this study intended to change their practice, but whether this was achieved was not measured.…”
Section: The Results In Relation To Other Studiesmentioning
confidence: 95%
“…It can be questioned if a short course of 16 hours would change the communication practice of pharmacists. However, a study from Japan has shown that community pharmacists can become more empathetic and have more satisfied patients after eight hours of simulation training (Tanuma et al, 2019). The pharmacists in this study intended to change their practice, but whether this was achieved was not measured.…”
Section: The Results In Relation To Other Studiesmentioning
confidence: 95%
“…Validation of a reorganized training program using a cognitive behavioral therapy approach to enable community pharmacists to provide empathic patient counseling (Tanuma et al, 2019) Formación teórica Juego de roles Empatía hacia las personas enfermas Programa de formación en habilidades comunicativas básicas. Juego de roles, utilizando 2 escenarios, un paciente con diabetes y un paciente hipertenso.…”
Section: Universidad Enfermeríaunclassified